2004
DOI: 10.5507/bp.2004.044
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Amphotericin B Deoxycholate or Amphotericin B Colloidal Dispersion on Renal Tubule Epithelium in Rat

Abstract: Amphotericin B deoxycholate (AmB) or Amphotericin B colloidal dispersion (ABCD) are used in clinics for the treatment of systemic fungal infections. The goal of our study was to compare the nephrotoxicity of these drugs in rat kidney. The effects of AmB and ABCD on the ultrastructure of the epithelium of renal tubules were studied and evaluated using morphometric and statistical methods. Two groups of 3 animals were established: group 1 was treated with AmB desoxycholate and group 2, to which ABCD was applied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Our data demonstrated that vitamin D deficient animals treated with AmB/LE presented impaired renal function, evidenced by lower GFR, higher plasma urea concentration, hyperphosphaturia, hypermagnesuria, proteinuria and mild tubular injury. It is well known that AmB-induced nephrotoxicity is due to the interaction of AmB with sterols from cell membranes, resulting in pore formation, defected electrolyte flux and loss of cell viability [3,17,18]. Furthermore, experimental and clinical trials have reported that treatment with AmB leads to denuded basement membrane, intratubular casts and tubular cell necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrated that vitamin D deficient animals treated with AmB/LE presented impaired renal function, evidenced by lower GFR, higher plasma urea concentration, hyperphosphaturia, hypermagnesuria, proteinuria and mild tubular injury. It is well known that AmB-induced nephrotoxicity is due to the interaction of AmB with sterols from cell membranes, resulting in pore formation, defected electrolyte flux and loss of cell viability [3,17,18]. Furthermore, experimental and clinical trials have reported that treatment with AmB leads to denuded basement membrane, intratubular casts and tubular cell necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Classical amphotericin B has disrupted the function of tubular and vascular smooth muscle cells by changing the permeability of cell membranes and leads to various tubular transport defects and vasoconstriction on blood vessels Sun et al;Larabi et al, 2004;Deray, 2002;Wasan et al, 1990;Krejcírová et al, 2004). It has been established that lipid based amphotericin B is responsible from transforming cell morphology, function and intracellular transport system by the toxic effect of the amphotericin B molecule Sawaya et al, 1995).…”
Section: Discussionmentioning
confidence: 99%